Combinatorial process optimization methodology and system - PHATAK PRASHANT B (2013)
A method for obtaining an optimized process solution from a set of design of experiments in a cost effective manner is provided. An actual experiment is performed and data from the experiments is obtained. Through statistical analysis of the data, coefficients are obtained. These coefficients are input into an experiment simulator where input parameters and conditions are combined with the coefficients to predict an output for the input parameters and conditions. From simulated results, conclusions can be drawn as to sets of input parameters and conditions providing desired results. Thereafter, physical experiments utilizing the input parameters and conditions may be performed to verify the simulated results.